Multimodal smoking cessation treatment combining repetitive transcranial magnetic stimulation, cognitive behavioral therapy, and nicotine replacement in veterans with posttraumatic stress disorder: A feasibility randomized controlled trial protocol. - Jonathan R Young; Carri S Polick; Andrew M Michael; Moritz Dannhauer; Jeffrey T Galla; Mariah K Evans; Addison Troutman; Angela C Kirby; Michelle F Dennis; Claire W Papanikolas; Zhi-De Deng; Scott D Moore; et al. (PLoS ONE)
Tobacco-related deaths remain the leading cause of preventable death in the United States. Veterans suffering from posttraumatic stress disorder (PTSD)-about 11% of those receiving care from the Department of Veterans Affairs (VA)-have triple the risk of developing tobacco use disorder (TUD). The most efficacious strategies being used at the VA for smoking cessation only result in a 23% abstinence rate, and veterans with PTSD only achieve a 4.5% abstinence rate. Therefore, there is a critical need to develop more effective treatments for smoking cessation. Recent studies suggest the insula is integrally involved in the neurocircuitry of TUD. Thus, we propose a feasibility phase II randomized controlled trial (RCT) to study a form of repetitive transcranial magnetic stimulation (rTMS) called intermittent theta burst stimulation (iTBS). iTBS has the advantage of allowing for a patterned form of stimulation delivery that we will administer at 90% of the subject's resting motor threshold (rMT) applied over a region in the right post-central gyrus most functionally connected to the right posterior insula. We hypothesize that by increasing functional connectivity between the right post-central gyrus and the right posterior insula, withdrawal symptoms and short-term smoking cessation outcomes will improve. Fifty eligible veterans with comorbid TUD and PTSD will be randomly assigned to active-iTBS + cognitive behavioral therapy (CBT) + nicotine replacement therapy (NRT) (n = 25) or sham-iTBS + CBT + NRT (n = 25). The primary outcome, feasibility, will be determined by achieving a recruitment of 50 participants and retention rate of 80%. The success of iTBS will be evaluated through self-reported nicotine use, cravings, withdrawal symptoms, and abstinence following quit date (confirmed by bioverification) along with evaluation for target engagement through neuroimaging changes, specifically connectivity differences between the insula and other regions of interest.